Enhanced Therapeutic Potential of Paclitaxel-Loaded Niosomes on Ovarian Cancer Cell Line - Fardpour, Maryam; Falahi Robattorki, Farnoush; Sarabi, Hossein; Zarazvand, Farjad; Arvand, Sara; Saegh, Alireza (Asian Pacific Journal of Cancer Biology, 2025)
Background: Paclitaxel is a widely used chemotherapeutic agent for ovarian cancer treatment; however, its clinical application is limited by poor solubility and severe side effects. Niosomes, non-ionic surfactant vesicles, have emerged as a promising nanocarrier for targeted drug delivery. This study investigates the enhanced therapeutic potential of paclitaxel-loaded niosomes in ovarian cancer cell line. Methods: Paclitaxel-loaded niosomes were prepared using the thin-film hydration method and characterized for size, zeta potential, and polydispersity index (PDI). The morphology of the niosomes was evaluated by scanning electron microscopy (SEM). Cytotoxicity of paclitaxel-loaded niosomes was assessed using the MTT assay on ovarian cancer cell line (A2780S) after 24 and 48 hours of incubation. The results were compared with free paclitaxel to evaluate the effect of the niosomal formulation on drug efficacy. Results: The paclitaxel-loaded niosomes exhibited a mean size of approximately 285 nm, a PDI of 0.44, and a negative zeta potential of -21 mV. SEM images confirmed the spherical morphology of the niosomes. The MTT assay results showed a significant increase in cytotoxicity in the niosomal formulation compared to free paclitaxel at both 24 and 48 hours (p < 0.05, p < 0.01), indicating enhanced therapeutic efficacy. Conclusion: Paclitaxel-loaded niosomes demonstrate improved drug delivery and enhanced cytotoxicity in ovarian cancer cell lines. The results suggest that niosomal paclitaxel could be a promising strategy for improving the therapeutic potential of paclitaxel in ovarian cancer treatment. Further in vivo studies are warranted to confirm these findings and explore the clinical applicability of niosomal formulations.